The effect of mandibular flexure on the design of implant-supported fixed restorations of different facial types under two loading conditions by three-dimensional finite element analysis - Gao, Jing; Li, Xuejing; He, Jing; Jiang, Lulu; Zhao, Baohong (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Investigating the biomechanical effects of mandibular flexure (MF) on the design of implant-supported fixed restorations in edentulous jaws of different facial types. Methods: Three-dimensional finite element models were established to analyze mandibular displacement and stress distribution of implant-supported fixed restorations (four or six implants, different implant number and sites, the design of the superstructure across the dental arch in one or two or three pieces, under the loading conditions of maximum opening or right unilateral molar occlusion) in mandibular edentulous patients of three different facial types (brachiofacial, mesofacial, and dolichofacial type). Results: Brachyfacial type presented higher mandibular flexure and stress in the overall restorative system, followed by the mesofacial and dolichofacial type. During jaw opening and occlusal movements, the 1-piece framework showed the lowest bone stress values surrounding the anterior implants and gradually increased to the distal position, 3-piece framework shows the highest stress values for peri-implant bones. And the split-framework could greatly increase the stress on abutments and framework. Moreover, fixed implant prostheses with cantilevers can generate high amounts of biomechanical stress and strain on implants and surrounding bone. The bone surrounding the anterior implant increased in stress values as the most distal implants were more distally located regardless of framework. The zirconia framework demonstrated the higher stresses compared with titanium. Conclusion: The design of edentulous fixed implant-supported restorations can be optimized for facial types. For patients of brachiofacial type or with high masticatory muscle strength, the non-segmented framework without cantilever provides an optimal biomechanical environment.